Gross Total vs. Subtotal Resection on Survival Outcomes in Elderly Patients With High-Grade Glioma: A Systematic Review and Meta-Analysis - Han, Qian; Liang, Hengpo; Cheng, Peng; Yang, Hongjie; Zhao, Pingfan (Frontiers in Oncology, 2020)
Background: The optimal strategy for the management of high-grade glioma in the elderly (≥60.0 years) remains controversial, especially regarding the effects of surgical extent on survival outcomes. The purpose of this study was to compare gross total resection (GTR) with subtotal resection (STR) for treatment effects in elderly patients with high-grade glioma. Methods: Three electronic databases were systematically searched, including PubMed, EmBase, and the Cochrane library, from inception to August 2018. Hazard ratios (HRs) or odds ratios (ORs) with corresponding 95% confidence intervals (CIs) were used to express summary effect estimates using the random-effects model. Nineteen retrospective observational studies involving a total of 10,815 elderly patients with high-grade glioma were included in this meta-analysis. Results: The summary results indicated GTR was associated with a significant improvement in overall survival (OS) compared with STR (HR=0.70; 95%CI 0.64-0.77). In addition, elderly patients administered GTR showed lower risk of 3-month mortality (OR=0.47; 95%CI 0.24-0.93), 6-month mortality (OR=0.38; 95%CI 0.26-0.56), 9-month mortality (OR=0.35; 95%CI 0.25-0.49), and 1-year mortality (OR=0.40; 95%CI 0.29-0.56). Pooled OS data differed when stratified by publication year, country, sample size, disease status, and study quality. Conclusion: GTR seems to be more effective than STR in achieving longer survival in elderly patients with high-grade glioma.